Stray bullets (1995), volume 2 ebook Somewhere out west. - Lapham, David (Stray Bullets (1995), 2015)
Somewhere out West is a town no one knows about--a desert town--whose inhabitants wait for the day a great earthquake will bring them beachfront property. Here, three desperate friends on the run from the Mob and a young runaway Virginia Applejack will try to escape the nightmares of their pasts. They'll band together to battle the demons that threaten to destroy them from within while taking on a corrupt town full of sex, drugs, and inbreeding. Eventually, they'll be forced to make horrifying choices when their dark pasts finally catch up with them.... Collects STRAY BULLETS #8-14.. Author: David Lapham. Illustrator: David Lapham . 2015 David Lapham.